2020
DOI: 10.1371/journal.pone.0229578
|View full text |Cite
|
Sign up to set email alerts
|

Is useful research data usually shared? An investigation of genome-wide association study summary statistics

Abstract: Primary data collected during a research study is often shared and may be reused for new studies. To assess the extent of data sharing in favourable circumstances and whether data sharing checks can be automated, this article investigates summary statistics from primary human genome-wide association studies (GWAS). This type of data is highly suitable for sharing because it is a standard research output, is straightforward to use in future studies (e.g., for secondary analysis), and may be already stored in a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…This underscores the need for PRS-RS to clearly and specifically define meaningful aspects of PRS development, testing, and intended clinical use. However, these deficits in reporting are not unique to PRS; previous reports of underreporting have found that 77% of GWAS publications in 2017 did not share summary statistics 65 and 4% of GWAS do not report any relevant ancestry information 1 . In line with the push towards a culture of reproducibility and open data in genomics, we as the ClinGen Complex Disease Working Group and PGS Catalog joined to create a set of reporting standards ( Table 1 ) specifically tailored to PRS research based on multidisciplinary and international expert opinion for tailoring previous standards.…”
Section: Using the Prs-rs And Pgs Catalog To Improve Prs Research Andmentioning
confidence: 93%
“…This underscores the need for PRS-RS to clearly and specifically define meaningful aspects of PRS development, testing, and intended clinical use. However, these deficits in reporting are not unique to PRS; previous reports of underreporting have found that 77% of GWAS publications in 2017 did not share summary statistics 65 and 4% of GWAS do not report any relevant ancestry information 1 . In line with the push towards a culture of reproducibility and open data in genomics, we as the ClinGen Complex Disease Working Group and PGS Catalog joined to create a set of reporting standards ( Table 1 ) specifically tailored to PRS research based on multidisciplinary and international expert opinion for tailoring previous standards.…”
Section: Using the Prs-rs And Pgs Catalog To Improve Prs Research Andmentioning
confidence: 93%
“…This contrasts with fields such as biodiversity, where organism prevalence data can be a primary research output, so data citations might be an important way to recognize the usefulness of a nonpublishing scientist's work. In fields like genomics, however, data can be extremely time-consuming to collect and valuable, but may not be commonly shared (Thelwall, Munafo et al, 2020), which is needed to encourage reuse and ultimately data citation.…”
Section: Open Data and Software Citationmentioning
confidence: 99%
“…However, there is still room for improvement. For instance, one group of researchers found that, within a sample comprising one-third of the genome-wide association studies published between 2010 and 2017, only 13% reported the location of their complete sets of summary data [7].…”
Section: Types Of Research Transparencymentioning
confidence: 99%